A doppio senso: istruzioni su come orientarsi nelle immagini astrologiche di Palazzo Schifanoia - Marco Bertozzi (2018)
In the “Sala dei Mesi” of Palazzo Schifanoia the months and the zodiacal constellations go from right to left, while the decans (three for every sign) go in the opposite direction. This problem was not clarified by Aby Warburg in his well-known essay Italian Art and International Astrology in the Palazzo Schifanoia of Ferrara (1912). The purpose of this paper is to investigate the reasons of this double direction.